PROFIL ANTROPOMETRI DAN KECEPATAN RENANG 50 METER ATLET RENANG KOTA TANJUNG PINANG - Andri Gemaini; Anton Komaini; Abu Bakar (JURNAL STAMINA, 2019)
The problem in this study is that there is no description yet about the physical condition capabilities of Tanjung Pinang City Athletes. This study aims 1) To find out the Anthropometry of Tanjung Pinang City Swimming athletes and 2) To find out the 50-meter swimming speed Freestyle of Tanjung Pinang City Swimming athletes. This type of research is descriptive research. The population in this study were all athletes registered in Tanjung Pinang PRSI. Which amounted to 37 people. The sampling technique was taken by purposive sampling. All male athletes who actively carry out exercises routinely and often participate in competition events at the regional level, amounting to 20 people. To obtain research data on the ability of the physical condition of the athletes in Tanjung Pinang City Swimming, a number of tests are conducted: body, arm length, leg length, palm width, and measuring swimming speed in the sample. The data analysis technique is using descriptive statistics with percentage techniques. Based on the results of data analysis shows that the Anthropometry variable owned by Tanjung Pinang City swimmer athletes are 1) The height of Tanjung Pinang City swimmer athletes is included in the category of less than 8 people (40%), 2) The arm length of Tanjung Pinang City swimmer athletes is included in the category good number of 8 people (40%), 3) The length of the limbs of swimming athletes in Tanjung Pinang City are included in the medium category amounting to 10 people (50%), 4) The width of the palms of the swimming athletes of Tanjung Pinang City are included in the moderate category totaling 8 people (40% ) and speed variables owned by swimming athletes in Tanjung Pinang City are included in the medium category amounting to 8 people (40%).